Theoretical and Experimental Comparison of Three Pumping Methods for Thulium Fiber Lasers for Low-Output Power (<10 W) - Anna Mauro; Valentina Serafini; Chiara Bellezza Prinsi; Matteo Cavagnetto; Luca Maggio Tanasi; Sabina Zaimovic; José Maria Blanco Triana; Gabriella Motta; Guido Perrone (Photonics)
Over the last decade, the number of demonstrations of Tm-doped fiber lasers has increased rapidly thanks to the applications of 2 <semantics>μ</semantics>m fiber laser in sensing, surgery, and polymer processing. In the literature, there is plenty of evidence that increasing the output power and the efficiency of this class of fiber lasers is of interest to the scientific and industrial communities. This article presents a theoretical and experimental study on three possible pumping methods for a Tm-doped fiber laser: out-of-band pumping, using a semiconductor-based module emitting at 793 nm; in-band pumping, using an ad hoc homemade fiber laser emitting at 1600 nm; an intracavity configuration, in which in the pump light is generated within the laser cavity itself. This work demonstrates how applying alternative pumping methods does not lead to significant improvements in laser performance without first taking into account the losses introduced in the system when switching from a cladding-pumped to a core-pumped configuration.